2017
DOI: 10.1016/j.ajog.2017.01.001
|View full text |Cite|
|
Sign up to set email alerts
|

Is middle cerebral artery Doppler related to neonatal and 2-year infant outcome in early fetal growth restriction?

Abstract: In a monitoring protocol based on ductus venosus and cardiotocography in early fetal growth restriction (26-31 weeks of gestation), the impact of middle cerebral artery Doppler and its ratios on outcome is modest and less marked than birthweight and delivery gestation. It is unlikely that middle cerebral artery Doppler and its ratios are informative in optimizing the timing of delivery in fetal growth restriction before 32 weeks of gestation. The umbilicocerebral ratio allows for a better differentiation in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 47 publications
4
74
1
1
Order By: Relevance
“…The main strength of our analysis is that the effects of antenatal steroids on Doppler indices and the CTG-STV were evaluated in a large population of early severe FGR fetuses followed up longitudinally until delivery. We analyzed the UC ratio rather than the cerebroplacental ratio (CPR), as we previously demonstrated that the former allows for better discrimination in the abnormal range [29]. A limitation is that the evaluation of the effects of betamethasone on fetal Doppler and the CTG-STV was not the aim of the TRUFFLE study [8].…”
Section: Discussionmentioning
confidence: 99%
“…The main strength of our analysis is that the effects of antenatal steroids on Doppler indices and the CTG-STV were evaluated in a large population of early severe FGR fetuses followed up longitudinally until delivery. We analyzed the UC ratio rather than the cerebroplacental ratio (CPR), as we previously demonstrated that the former allows for better discrimination in the abnormal range [29]. A limitation is that the evaluation of the effects of betamethasone on fetal Doppler and the CTG-STV was not the aim of the TRUFFLE study [8].…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that no included study provided data to assess the predictive ability of CPR for adverse neurodevelopmental outcome in pregnancies with suspected FGR. A secondary analysis of the TRUFFLE study 65 reported that CPR was not associated with neurodevelopmental impairment at 2 years' corrected age in fetuses with suspected early-onset growth restriction 66 . Two studies reported similar results for decreased MCA-PI in suspected FGR 67,68 .…”
Section: Main Findingsmentioning
confidence: 99%
“…There were weak associations between middle cerebral artery (MCA) Doppler and short‐term neonatal outcome, and between MCA Doppler and umbilical:cerebral ratio with 2‐year neurodevelopmental outcome. Although these indices may be informative in understanding the pathophysiological process, they are of no proven benefit in the monitoring or management strategy before 32 weeks' gestation.…”
Section: What Was the Truffle Study?mentioning
confidence: 99%